Analysis of patient satisfaction with electronic medical record services at general hospital: A cross-sectional study - Muhamad Tito Aristian; Nani Sari Murni; Chairil Zaman (School of Health Sciences Al-Ma'arif, 2025)
Background Patient satisfaction is a critical indicator for evaluating the quality of healthcare services, including electronic medical record (EMR) services in hospitals. As one of the main healthcare providers in Ogan Komering Ilir Regency, Tugu Jaya Regional General Hospital has not yet provided specific data regarding patient satisfaction in its registration unit. Objective This study aimed to analyze factors associated with patient satisfaction with electronic medical record services in the registration unit. Methods A quantitative study with a cross-sectional design was conducted. The study population consisted of all patients registered at the hospital registration unit between January and April 2025. A total of 93 respondents were selected using purposive sampling based on inclusion and exclusion criteria. Data were collected through a structured questionnaire that had been tested for validity and reliability. Data analysis was performed using univariate analysis, bivariate analysis with Chi-square test, and multivariate analysis with multiple logistic regression. Results The findings indicated that education, tangibles, empathy, and assurance were significantly associated with patient satisfaction (p<0.05). Multivariate analysis revealed that tangibles (OR=3.93; 95% CI: 1.44–10.74) and assurance (OR=3.61; 95% CI: 1.15–11.31) were the dominant predictors of patient dissatisfaction. Conclusion Patient satisfaction with electronic medical record services in the registration unit of general hospital was significantly influenced by the dimensions of tangibles, empathy, and assurance, with tangibles identified as the dominant factor. Efforts to improve patient satisfaction should prioritize enhancing physical facilities, fostering empathetic attitudes, and strengthening trust through professional and reliable services.